Combining hybrid and opaque scintillator techniques in the search for double beta plus decays - Manuel Böhlers; Sebastian Böser; Magdalena Eisenhuth; Cloé Girard-Carillo; Kitzia M. Hernandez Curiel; Bastian Keßler; Kyra Mossel; Veronika Palušová; Stefan Schoppmann; Alfons Weber; Michael Wurm (European Physical Journal C: Particles and Fields)
Abstract Double beta plus decay is a rare nuclear disintegration process. Difficulties in its measurement arise from suppressed decay probabilities, experimentally challenging decay signatures and low natural abundances of suitable candidate nuclei. In this article, we propose a new detector concept to overcome these challenges. It is based on the first-time combination of hybrid and opaque scintillation detector technology paired with novel light read-out techniques. This approach is particularly suitable for detecting positrons (beta plus) signatures. We expect to discover two-neutrino double beta plus decay modes within 1 tonne-week exposure and are able to probe neutrinoless double beta plus decays at several orders of magnitude improved significance compared to current experimental limits.